Insurance and Rural Welfare: What can Panel Data tell us? - Chris Elbers; Jan Willem Gunning; Lei Pan (Tinbergen Institute, 2007)
Assessing the scope for insurance in rural communities usually requires a structural model of household behavior under risk. One of the few empirical applications of such models is the study by Rosenzweig and Wolpin (1993) who conclude that Indian farmers in the ICRISAT villages would not benefit from the introduction of formal weather insurance. In this paper we investigate how models such as theirs can be estimated from panel data on production and assets. We show that if assets can take only a limited number of values the coefficients of the model cannot be estimated with reasonable precision. We also show that this can affect the conclusion that insurance would not be welfare improving.
Keywords: C51; D91; 330; Structural estimation; discrete choices; insurance; Risikopräferenz; Privater Haushalt; Ländlicher Raum; Indien